Analisis Watak Tokoh dalam Novel Kitab Cinta Yusuf Zulaikha Karya Taufiqurrohman al-Azizi - Muhammad Hasbullah Ridwan (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The focus of this research is: (1) to analyze the character of the character through what is done, (2) to analyze the character of the character through his speech, (3) to analyze the character of the character through the physical description, (4) to analyze the character of the character through his thoughts. This study uses an intertextual approach, which is a study of the number of texts that have certain relationships. The source of this research data is a novel entitled book of Love Yusuf Zulaikha by Taufiqurrohman Al-Azizi. Conclude this research (1) through what he did get the picture that, Yusuf has a patient, religious nature, began to small he was taught religion by his father and broad insight even the only high school graduate knowledge is not inferior to the lecture because his hobby likes reading and discussing with his friends. (2) through his utterance, the illustration is that Joseph is very careful in speaking almost all words that come out of his mouth are wise and orderly. (3) through the physical description in obtaining the picture that Joseph has a handsome and beautiful face, his face glowing everybody is happy to see him, but Yusuf is so humble he is never arrogant about it. (4) through his thoughts obtained the picture that not in a hurry in making decisions and always ask for guidance to Allah SWT.